Embedding Chaplaincy Services in Primary Care for Immigrants, Refugees and Asylum Seekers: A Boston Pilot Intervention - Kimball, Sarah L. (Journal of religion and health, 2023)
This Boston-based pilot research was an exploratory study that integrated outpatient chaplaincy into a refugee and immigrant health primary care clinic. Patients were screened for spiritual distress and offered a meeting with chaplaincy interns. Forty-eight patients were seen in clinic, 28 were screened, and 9 met with a chaplain. Most frequent domains of spiritual distress were grief (n = 8), feelings of abandonment (n = 5), guilt (n = 4), betrayal (n = 4), fear of death (n = 3), shame (n = 3), and trust (n = 3). Faith was relevant to treatment decision-making for 6 patients. It was found that outpatient chaplaincy services are a feasible intervention to address spiritual distress in immigrant and refugee patients.